2023
DOI: 10.1158/1078-0432.ccr-22-3526
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive ctDNA Measurements Improve Prediction of Clinical Outcomes and Enable Dynamic Tracking of Disease Progression in Advanced Pancreatic Cancer

Abstract: Purpose: Circulating tumor DNA (ctDNA) has emerged as a promising tumor-specific biomarker in pancreatic cancer, but current evidence of the clinical potential of ctDNA is limited. In this study, we used comprehensive detection methodology to explore the utility of longitudinal ctDNA measurements in patients with advanced pancreatic cancer. Experimental Design: A targeted eight-gene next-generation sequencing panel was used to detect point mutations and copy number aberrations (CNAs) in ctDNA from 324 pre-trea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…We found that, using longitudinal analyses of combined mutations of KRAS , TP53 , CDKN2A , SMAD4 , and ARID1A , 48% of the patients had a ctDNA progression earlier than radiologic progression, and 42% a ctDNA progression earlier than CA19-9 progression, both with a median lead time of about 2 months, which is supported by previous reports [ 46 , 79 ]. In resected PDAC, ctDNA could predict recurrence with a median lead time of 84 days.…”
Section: Discussionsupporting
confidence: 89%
“…We found that, using longitudinal analyses of combined mutations of KRAS , TP53 , CDKN2A , SMAD4 , and ARID1A , 48% of the patients had a ctDNA progression earlier than radiologic progression, and 42% a ctDNA progression earlier than CA19-9 progression, both with a median lead time of about 2 months, which is supported by previous reports [ 46 , 79 ]. In resected PDAC, ctDNA could predict recurrence with a median lead time of 84 days.…”
Section: Discussionsupporting
confidence: 89%
“…Our PNA clamp PCR assay only detects mutations in codons 12 and 13 of KRAS , but these variants constitute more than 95% of the reported KRAS mutations in PDAC [ 33 ]. We also analysed most of the samples in the current study using a sequencing‐based approach and found that 95% of the mutations in KRAS occur in codons 12 and 13 [ 34 ]. Overall, we observed 89% concordance between the two methods for mutations in codon 12 of 13 ([ 34 ] and results not shown), emphasising the robustness of the PNA clamp method.…”
Section: Discussionmentioning
confidence: 99%
“…We also analysed most of the samples in the current study using a sequencing‐based approach and found that 95% of the mutations in KRAS occur in codons 12 and 13 [ 34 ]. Overall, we observed 89% concordance between the two methods for mutations in codon 12 of 13 ([ 34 ] and results not shown), emphasising the robustness of the PNA clamp method. Moreover, the amount and quality of cfDNA input influences ctDNA detection [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach complements and potentially surpasses other circulating biomarkers in PDAC, such as ctDNA. Even with the limitation of our study restricting analysis to 5% of DLA products, our CS-CTC detection align with ctDNA detection rates even in advanced PDAC [ 21 , 22 ]. This can be attributed to minimal cfDNA shedding in PDAC and the challenges associated with obtaining tissue in non-operable cases for tumor-informed approaches.…”
Section: Discussionmentioning
confidence: 52%